Willingness to Pay for Improving the Quality of Pasir Putih Beach Tourism Objects in Manokwari Regency - Sirfefa, Ismail; Wurarah, Rully Novie; Elungan, Oktavianus O. (AIBPM Publisher, 2023)
This study examines tourists’ willingness to pay (WTP) related to efforts to develop and improve the environmental quality of Pasir Putih Beach. A sample of 100 respondents found that their overall willingness to contribute amounted to IDR 13,100,000, with an average individual willing to contribute IDR 131,000. Further analysis revealed that income and education factors positively and significantly influence WTP. This indicates that individuals with higher income and education tend to contribute more to the sustainability of the tourist attraction. However, perception factors related to facilities and cleanliness and the distance of residence from the tourist attraction did not show a significant influence. Most respondents prefer to pay Rp.100,000 to Rp.300,000, while no one is willing to contribute in the Rp.400,000-500,000 range. These results indicate the urgency for managers and local governments to consider infrastructure and facility improvements at Pasir Putih Beach as a strategy to increase WTP and financial support from tourists.